(untitled) (Ameghiniana, 2023)
A 209 m-thick sedimentary succession exposed at Estancia Redonda Chica locality (northeastern Patagonia, Argentina) includes both the Gaiman Formation (Early Miocene) and the Puerto Madryn Formation (Late Miocene). Based on the sedimentologic analysis, the Gaiman Formation is interpreted as accumulated in a marine inner shelf to shoreline environment, whereas an estuarine to terrestrial environment is interpreted for the Puerto Madryn Formation. Fifteen samples were processed and analyzed for diatoms, providing for the first time a micropaleontological record for these units, allowing us to go deeper into the paleoenvironmental interpretations. Fourteen diatom species, two diatom genera, and chrysophyte stomatocysts were identified. The dominant diatom elements among the samples are Paralia sulcata, Lemnicola hungarica, Cocconeis placentula, and Pseudopodosira sp., together with chrysophyte stomatocysts. Paleoecological information drawn from diatom assemblages is consistent with paleoenvironmental interpretations based on sedimentological analysis for both units. However, diatom analysis for the Gaiman Formation suggests a strong freshwater influence in an inner shelf environment, which went unnoticed by utilizing other proxies. We suggest a high-productivity marine zone may have developed as a consequence of nutrient supply from rivers favoring diatom growth. This could explain the unique great abundance of macroinvertebrates and marine vertebrates preserved in the sedimentary succession.